Extraction optimization and amplification of oil palm DNA: leaves at different phases of development - Andrade Bomfim, Joao Pedro de [UNESP]; Lima, Laiana Pinheiro de; Ferreira de Melo, Clausio Antonio; Correa, Ronan Xavier; Gaiotto, Fernanda Amato; Magalhaes Barbosa, Antonia Marlene (Centro Pesquisas Florestais, Ufsm, 2020)
The objective of this study was to optimize and establish a protocol to enhance the quality and quantity of deoxyribonucleic acid (DNA) extracted from leaves under different development stages and conservation conditions collected from mature plants and seedlings. Furthermore, we aimed to standardize the polymerase chain reaction (PCR) and select an inter simple sequence repeat (ISSR) marker for Elaeis guineensis (oil palm). The modified cetyltrimethylammonium bromide (CTAB) protocol, which used ri-mercaptoethanol (0.3%) and polyvinylpyrrolidone (PVP 3%) supplementation in the extraction buffer and 10 % CTAB with 1.4 M NaCI for a 20-min incubation at 65 degrees C, resulted in improved DNA quality and quantity. However, this protocol presented variable results among samples, probably due to variations in leaf degradation levels and development stages. The two PCR protocols (I and H) for amplifying the DNA, differed mainly in the presence or absence of bovine serum albumin (BSA) and primer concentration. Al though, a correlation between PCR amplification and the qualiw of the DNA extracted from leaves was not established, the addition of BSA (0.075 mg/mL) and the highest primer concentration (0.5 pmol) (protocol II) resulted in more intense and distinguishable bands on gel electrophoresis. DNA quality was essential for a satisfying amplification, considering all the samples. The use of protocol II allowed the selection of five primers: UBC 807, 810, 812, 834, and 848; these were used in the amplification of the DNA extracted from 13 families consisting of one parental plant and eight progenies each.
Keywords: Elaeis guineensis; PCR; ISSR